PERAN KINERJA LINGKUNGAN DALAM MEMODERASI PENGARUH UKURAN PERUSAHAAN, LEVERAGE DAN PROFITABILITAS TERHADAP PENGUNGKAPAN LINGKUNGAN - Abdurrahman; Wahyudin, Agus (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2020)
This study aims to obtain empirical evidence of the effect of firm size, leverage and profitability on environmental disclosure with environmental performance as a moderator.The population of this research is 91 high-profile companies listed on the Indonesia Stock Exchange (BEI) from 2014 to 2016.The sampling technique is purposive sampling and 17 sample companies with a total of 45 units of analysis.The data analysis technique in this study is descriptive analysis and moderated regression analysis to test the hypothesis.The findings in this study indicate that company size, leverage and profitability have no significant effect on environmental disclosure.The moderating variable in the form of environmental performance can only moderate the effect of leverage on environmental disclosure